PENGARUH KEPUASAN, KEPERCAYAAN, DAN KOMITMEN TERHADAP LOYALITAS KONSUMEN TELEKOMUNIKASI - Arnold Japutra (Universitas Bunda Mulia, 2017)
This research is quantitative descriptive research with cross sectional study. The primary data is obtained from students of a university located in Jakarta Barat. The method of sampling is non probability sampling and the technique is judgmental sampling. The sample consisted of 300 respondent. The result of this research shows that there is a positive effect satisfaction to trust, there is a positive effect on trust to commitment, there is a positive effect commitment to loyalty, there is a positive effect satisfaction to loyalty and there is a positive effect trust to loyalty. Key Words- Satisfaction, Trust, Commitment, Loyalty